Diseases of Economic Importance in Feedlot Cattle in Sub-Saharan Africa: A Review with a Focus on Existing and Potential Options for Control - Kennedy Mwacalimba; Peter Kimeli; Raymond Tiernan; Erik Mijten; Tetiana Miroshnychenko; Barbara Poulsen Nautrup (Animals)
A large number of livestock are found in sub-Saharan Africa (SSA), including 20–25% of the world’s ruminants [...]